P3.08 Sti prevalence and correlates of moral judgment and belief of hiv transmission through casual contact in adolescents attending public high schools in two districts in panama. (8th July 2017) - Gabster, A; Arteaga, GB; Martinez, A; Mendoza, E; Dyamond, J; Castillero, O; Castillo, J; López, A; Mojica, N; Pascale, JM
Abstract : Introduction: Moral judgments (MJ) against people living with HIV (PLHIV), and belief of HIV transmission through casual contact (CC), lead in varying to degrees to social exclusion, discrimination, and violence. This study estimates the prevalence of HIV and other sexually transmitted infections (STI), and describes manifestations and correlates of MJ and CC among participants. Methods: A cross sectional study using multistage cluster sampling was conducted among public high school students, aged 14–19 years, in two districts in Panama City from August-November 2015 and June-August 2016. Participants self-administered a questionnaire and gave biological samples. Those who acknowledged prior sexual activity (PSA) were tested for HIV and other STI (syphilis, chlamydia, gonorrhoea, trichomoniasis, M. genitalium, and hepatitis B surface antigen). Results: Of the 1228 male and female participants, 57.7% of males and 58.5% of females reported PSA; 23.1% of participants reporting PSA had ≥1 positive STI test. Positive STI tests or PSA were not correlated with MJ or CC. Manifestations of MJ were found in 19.6% of participants; correlates include low confidence in personal HIV knowledge (AOR=2.5, 95% CI: 1.3–5.0) and belief that HIV+ classmates should be excluded from school (CES) (AOR=2.7 95% CI: 1.6–4.6). Almost half (48.8%) of participants answered affirmatively to 2–9 scenarios of transmission by CC. High confidence in personal HIV knowledge was protective for belief of transmission through CC (AOR=0.6, 95% CI: 0.4–0.9); participants with belief in CES were more likely to believe in transmission by CC (AOR=2.0 95% CI: 1.3–3.2). Conclusion: This study found high STI prevalence in public school adolescents from two districts in Panama City. Poor confidence in personal HIV knowledge and exclusion through CES were correlated with MJ of PLHIV, and belief in HIV transmission through CC. This study identifies the need for effective educational interventions to increase HIV transmission knowledge and decrease negative attitudes towards PLHIV. Support: : Funding for this study came from the Panamanian Ministry of Economics and Finance